Exposição de gametas, embriões e larvas de jundiá (Rhamdia quelen) ao 2,4-d e glifosato: efeitos sobre indicadores do equilíbrio redox e sobre a viabilidade da prole - Bernardi, Fernanda (2021)
Pesticides are products formulated used in the agricultural environment to control pests (insects, animals, plants, or fungi). In excavated ponds, the use of herbicides to eliminate all aquatic plants can reduce fish habitat, food supply, dissolved oxygen, and fish productivity. The objective of this work was to evaluate the effects of the herbicides 2,4-D, glyphosate, and the mixture of both on oxidative stress, genotoxicity, the rates of fertilization, hatching, larval normality, and on sperm parameters in silver catfish. Two experiments were carried out, which were distributed completely randomized experimental design, composed by ten treatments and three replications. The treatments consisted of using water with different concentrations of glyphosate (3.0; 6.0; 9.0 and 12.0 mg a.e. L-1), 2.4-D (5.0; 10.0; 20.0 and 30.0 mg a.e. L-1) and the mixture of both (5.0 mg a.e. L-1 of 2,4-D + 10.0 mg a.e. L-1 of glyphosate) both for the incubation of eggs and semen activation. The eggs and semen of the control group were incubated and activated in distilled water, respectively. Eggs incubated for 1 hour in fiberglass incubators were transferred to 24-well cell culture plates at a density of 5 eggs per well, containing 2 mL of contaminated water in each well. 12 hours after artificial fertilization, the fertilization rate was measured. The hatching rate was measured 38 hours after artificial fertilization. The rate of larval normality was measured 62 hours after artificial fertilization. Eggs incubated for 1 hour in fiberglass incubators were transferred to plastic containers containing 200 mL of contaminated water, at a density of 3.0 mL of eggs (401 ± 33 eggs) per plastic container. The larvae were collected 45 hours after artificial fertilization and, subsequently, analyzed the activity of the enzymes catalase (CAT), glutathione-S-transferase (GST), superoxide dismutase (SOD), lipoperoxidation (LPO), and protein carbonylation (PCO). Eggs incubated for 1 hour in fiberglass incubators were transferred to plastic containers containing 100 mL of contaminated water, at a density of 1.5 mL of eggs (173 ± 23 eggs) per plastic container. The larvae were collected 48 hours after artificial fertilization and, subsequently, DNA damage was quantified. Semen aliquots were evaluated by the CASA plugin (Computer Assisted Sperm Analysis) in free software. Sperm movement was assessed at 12 and 14 seconds after the start of sperm activation. The variables analyzed were: sperm motility, linearity, curvilinear velocity (VCL), average path velocity (VAP), straight-line velocity (VSL), and sperm velocity (VE). Exposure to glyphosate and the mixture of herbicides significantly decreased the fertilization of oocytes and the hatching of eggs. Water contaminated with 2,4-D did not affect fertilization and hatching rates. The different concentrations of 2,4-D and glyphosate, in addition to the mixture of both, did not affect the rates of larval normality. The activity of CAT, GST, LPO, and PCO were not altered in any of the tested concentrations of glyphosate, 2,4-D, and the mixture of herbicides. SOD activity was not evident in any of the treatments. Exposure to 2,4-D and the mixture of herbicides caused damage to the genetic material of larvae silver catfish. Exposure to glyphosate did not induce DNA strand break in larvae silver catfish. The herbicides 2,4-D, glyphosate, and the mixture of both were harmful to sperm motility. Linearity, VCL, VAP, VSL, and VE were not affected by the use of glyphosate, 2,4-D, and the mixture of herbicides. Our results show that although high concentrations of the herbicides were used, changes caused by them were detected in only some of the tested biomarkers.